Distribution of climate damages in convergence-consistent growth projections - Anthony Harding; Juan Moreno-Cruz; Martin Quaas; Wilfried Rickels; Sjak Smulders (Energy Economics, 2025)
Climate-econometric estimates assuming that climate changes affect economic growth result in larger projected damages than estimates restricting the effect to economic income levels. We show that the latter is consistent with neoclassical macroeconomic theory by explicitly accounting for income growth convergence in our empirical investigation. We show that accounting for convergence does not statistically change the point estimates capturing climate's macroeconomic effect, but it has significant implications for assessing the long term economic consequences of climate change. The magnitude and spread of long-term losses from climate change are reduced. Aggregated damages are found to be convex in the extent of climate change and are projected to continuously increase over time with on-going climate change, in contrast to growth-effects-only estimates where the gains experienced by the winners of climate change eventually surpass the losses incurred by the losers. For example, projections of climate change damages based on climate-econometric estimates by Burke et al., 2015 find that global warming could reduce average global incomes by 20% and drastically increase intercountry income inequality, reflected by a 118% increase in the Gini coefficient in 2100 under RCP8.5. We reestimate and project climate damages under the same scenario accounting for convergence and find global climate damages around 8.5% of global incomes and an increase in intercountry income inequality by 8% in 2100.
Keywords: Q54; O47; O44; C23; D63; Q56; 330; Climate change; Economic growth; Convergence